The refugee and migrant health “global competency standards for health workers”: results of a survey in general practitioner trainees in Sicily - Cimino, Livia; Pirrello, Alessandra; Casuccio, Alessandra; Costantino, Claudio; Graci, Davide; Piazza, Nicolò; Immordino, Palmira (Frontiers in Public Health, 2024)
Background Refugees and migrants may represent the most vulnerable communities in many societies. Health systems should be sensitive to needs of refugees and migrants. The document “The Refugee and Migrant Health: Global Competency Standards for Health Workers (the Standards)” identifies the competencies and areas of practice of health workers working with refugees and migrants. The aim of this study is to provide an analysis of these competences and training needs, identifying the educational priorities for the implementation of the Standards in Sicily, Italy. Methods A cross-sectional analytical pilot study was conducted by administering a questionnaire, in electronic format “Google Form ®,” to doctors attending the Medical Training Course for General Practitioners in Sicily (Italy). Data obtained were collected in a Microsoft Excel database and analyzed with IBM SPSS Software 24 version. Absolute and relative frequencies were calculated for relevant categorical variables. Univariate analysis of the selected variables was subsequently carried out. The significance level chosen was a p value <0.05 (two-tailed). Results A total of 192 General Practitioner (GP) trainees responded to the questionnaire. They were asked if their training course comprised a Global Health Course that included the topic of health protection and social and health care for migrant populations and the 65.4% of them answered “No” or “Do not Know.” GP trainees were also asked if they considered useful to include a Global Health Course dedicated to the management of patients with a migratory background within the training course in general medicine. Of the total 192 participants, 81.9% answered “Yes.” Overall, in a simple regression model, the perception of having addressed migrants’ health needs is positively correlated with having attended a Global Health Course (OR = 3.34 95%CI 1.2–9.1; p = 0.018). Conclusion This study identified educational priorities for the implementation of the Standards in Sicily for doctors attending the Medical Training Course for General Practitioners. We hope that the results of this study will guide and inform possible future projects to implement the Standards at a national level.